Significant improvement of Age-Related Macular Degeneration with Melanin Precursors (QIAPI 1®). Case Report - Arturo Solís Herrera; María del Carmen Arias Esparza; Martha P Solis-Arias (Journal of Clinical Research and Ophthalmology - Peertechz Publications, 2021)
Age-related macular degeneration is the first cause of blindness in cold countries in the last 70 years ago or more. In spite expensive therapeutics strategies like intraocular injections, so far, the incidence and prevalence of ARMD cannot be improved significantly. In this case report, we demonstrate that melanin is a fundamental part of macular biology and once is attended the recovery both anatomical and functional is significant.